Potential benefits of GLP-1 analogues and metformin in patients with osteoarthritis - Anna Skowronek; Martyna Piekarska; Katarzyna Dąbek; Michał Ochwat; Maria Sudoł; Gabriela Mierzwa; Aleksandra Kajtel; Tomasz Skowronek (Journal of Education, Health and Sport)
Introduction and purpose